Utility estimations of different health states of patients with type I, II, and III spinal muscular atrophy in China: A mixed approach study with patient and proxy-reported data - Hu, Jiahao; Zhu, Lin; Bao, Han; Liu, Yuhan; Xing, Huanping; Kang, Qi; Jin, Chunlin (Frontiers in Public Health, 2022)
Introduction Spinal muscular atrophy (SMA) is a rare autosomal-recessive neuromuscular disease. Health state utility values (HSUV) are used in health economic evaluation regarding the desirability of health outcomes such as a certain health state or change in health states over time. There is no utility data of Chinese patients with SMA. Materials and methods Vignettes were developed for 10 pediatric neurologists to value the utility of Chinese patients with Type I SMA. A mixed patient/proxy derived approach using EQ-5D-Y-3L, EQ-5D-3L, and CHU9D was adopted to estimate the HSUV data of patients with Type II and III SMA, including 112 patients and 301 caregivers. Result The utility of Type I SMA patients ranged from 0.19 to 0.72 with the health state improved from “permanent ventilation” to “walking”. The utility of children patients with Type II and III SMA derived from EQ-5D-Y-3L ranged from 0.33 to 0.82 while that derived from CHU9D ranged from 0.46 to 0.75. The utility of adult patients with Type II and III SMA measured by EQ-5D-3L ranged from 0.30 to 0.83. Conclusion The better health states the patients with SMA were in, the higher were the HSUV. The utilities derived from population with different age and disease subtypes were not statistically different when patients with SMA were in the same health states. We recommend further studies on the Chinese specific value set for EQ-5D-Y-3L and other PBMs for children to derive more robust utility data.